A large-scale assessment of two-way SNP interactions in breast cancer susceptibility using 46 450 cases and 42 461 controls from the breast cancer association consortium - Milne, Roger L.; Brenner, Hermann; Dieffenbach, Aida Karina; Hamann, Ute; Marmé, Frederik; Burwinkel, Barbara (Human molecular genetics, 2014)
Part of the substantial unexplained familial aggregation of breast cancer may be due to interactions between common variants, but few studies have had adequate statistical power to detect interactions of realistic magnitude. We aimed to assess all two-way interactions in breast cancer susceptibility between 70 917 single nucleotide polymorphisms (SNPs) selected primarily based on prior evidence of a marginal effect.
Advance access published on November 15, 2013
Gesehen am 09.09.2020